Implementasi Sumber Daya Penyimpanan Dinamis Pada Cloud - Lulus Bagos Hermawan; Sabriansyah Rizqika Akbar; Primantara Hari Trisnawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Along with the development of the era of human needs and dependence on computers increasingly large pekembangan modern technology world. Use of your own computer from various fields to solve computing problems from small to large scale. Can not be denied by the development of applications in the computer world requires a larger resource, so less efficient if only done with a physical machine only. Various ways are done to overcome this problem one of them with virtualization. In this research, the implementation of dynamic storage resource management in the cloud. Virtulasisation used in this research by using virtual box. Dynamic storage used in this research by implementing Logical Volume Management feature. The results of this study obtained a system that can make the addition of storage capacity dynamically and automatically without any downtime and rebooting on the system